Fundamentos da responsabilidade do Estado em matéria tributária - Becker, Josiane (2017)
The current research, carried out by the analytical hermeneutical dogmatic method aims to analyze the responsibility of the State due to damages caused for its own tax activity. The State, as a subject of rights and obligations, is not independent from the guiding principle of civil responsibility, enshrined in the Constitution, which imposes on those who cause damage to others the duty to repair. The responsibility of the State is established when, with an action or omission of the Legislative, Executive or Judiciary, it imposes an unlawful damage to taxable persons, that is, imposes a burden higher than the individuals or companies must bear. This is independent of the illegality of the state action. The normative injunction that impute to the State the obligation to indemnify is based on the study of the fiscal juridical relation as source of damages and on the characteristics that must meet the said damage, in order to be compensable. Here arises the doubt of the power-duty to demand a tribute to be - or not - contained a duty of state protection, whose violation gives rise to the responsibility of the State for the purposes of indemnification. In general terms, the resolution is in the constitutional command carved in Article 37, § 6, of the Federal Constitution, is applied to the undue damages originating from conduct of the State before acts of tax content, being, in addition to repairing the damage also necessary invalidating the act contrary to the legal system. The justification for the application of the constitutional norm lies in the principles of state responsibility, such as precaution, prevention, solidarity and equality, which protect the fundamental rights of individuals and guide the State to act within the limits imposed by the law. The study of the foundations of State responsibility in tax matters will appeal to the legal operators in the application of the rule and will serve as an aid in the defense of individuals against state abuses, as it reflects in the creation of an adequate means to protect taxpayers' rights and guarantees